1998
DOI: 10.1097/00000374-199803001-00005
|View full text |Cite
|
Sign up to set email alerts
|

Abnormality of Very Long-Chain Fatty Acids of Erythrocyte Membrane in Alcoholic Patients

Abstract: Profiles of very long-chain fatty acids were studied in the erythrocyte membrane of five alcoholic patients. We identified three fatty acids as cis-16-pentacosenoic acid (C25:1), cis-17-hexacosenoic acid (C26:1), and hexacosenoic acid (C26:1), and hexacosanoic acid (C26:0) by gas chromatography-mass spectrometry. The ratios of C26:1/C22:0, C26:0/C22:0, C24:1/C22:0, and C24:0/C22:0 were increased. These findings suggest that active oxygen species or free radicals generated by chronic alcohol consumption in alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Elevated levels of cerotic acid were previously reported in other diseases. Adachi et al [23] found higher levels of cerotic acid and hexacosenoic acid (26: 1) in erythrocyte membranes in alcoholic patients. According to these authors, this was a result of alcohol-induced interruption of peroxisomal beta-oxidation, a process involved in VLCFA metabolism [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of cerotic acid were previously reported in other diseases. Adachi et al [23] found higher levels of cerotic acid and hexacosenoic acid (26: 1) in erythrocyte membranes in alcoholic patients. According to these authors, this was a result of alcohol-induced interruption of peroxisomal beta-oxidation, a process involved in VLCFA metabolism [23].…”
Section: Discussionmentioning
confidence: 99%
“…Adachi et al [23] found higher levels of cerotic acid and hexacosenoic acid (26: 1) in erythrocyte membranes in alcoholic patients. According to these authors, this was a result of alcohol-induced interruption of peroxisomal beta-oxidation, a process involved in VLCFA metabolism [23]. Elevated serum levels of cerotic acid were also observed in X-linked adrenoleukodystrophy, an inherited disorder of peroxisomal metabolism characterized by deficient β-oxidation of saturated VLCFAs [24], as well as in other diseases associated with peroxisomal disorders [25].…”
Section: Discussionmentioning
confidence: 99%
“…, 2006), post‐menopausal hormone replacement therapy (Stark et al. , 2003) and alcoholism (Adachi et al. , 1998) among these.…”
Section: Introductionmentioning
confidence: 99%